2016
DOI: 10.1105/tpc.15.01045
|View full text |Cite|
|
Sign up to set email alerts
|

The Nuclear Ribonucleoprotein SmD1 Interplays with Splicing, RNA Quality Control, and Posttranscriptional Gene Silencing in Arabidopsis

Abstract: RNA quality control (RQC) eliminates aberrant RNAs based on their atypical structure, whereas posttranscriptional gene silencing (PTGS) eliminates both aberrant and functional RNAs through the sequence-specific action of short interfering RNAs (siRNAs). The Arabidopsis thaliana mutant smd1b was identified in a genetic screen for PTGS deficiency, revealing the involvement of SmD1, a component of the Smith (Sm) complex, in PTGS. The smd1a and smd1b single mutants are viable, but the smd1a smd1b double mutant is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 39 publications
0
63
1
Order By: Relevance
“…Sm proteins can also have functions in RNA metabolism beyond splicing of primary transcripts (Lu et al 2014;Xiong et al 2015). In Arabidopsis, SmD1 participates in pre-mRNA splicing, RNA quality control, and post-transcriptional gene silencing (Elvira-Matelot et al 2016).…”
Section: Smfamentioning
confidence: 99%
“…Sm proteins can also have functions in RNA metabolism beyond splicing of primary transcripts (Lu et al 2014;Xiong et al 2015). In Arabidopsis, SmD1 participates in pre-mRNA splicing, RNA quality control, and post-transcriptional gene silencing (Elvira-Matelot et al 2016).…”
Section: Smfamentioning
confidence: 99%
“…To date, however, only two putative Arabidopsis Sms, SMD3 and SMD1, have been characterized. The analysis of smd3b and smd1b null mutants revealed that SMD3 and SMD1 are involved in plant development as well as in the processing of the few pre-mRNAs whose splicing patterns were examined (Swaraz et al, 2011;Elvira-Matelot et al, 2016). Nonetheless, whether they are functional Sm proteins that ensure precise levels of U snRNAs and what their relevance is in modulating pre-mRNA splicing at the genomic level is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, similar AS defects were shown between the prp8a mutant and RNAi-ASCO lines for pathogenrelated genes (Figs 6BC and EV10), indicating that the flg22 differential phenotype of RNAi-ASCO plants may be related to the interaction with the spliceosome components. Recently, we identified another core component of the spliceosome, SmD1b, linked to both AS and the recognition of aberrant ncRNAs to trigger gene silencing (Elvira-Matelot et al, 2016). Interestingly, ASCO expression levels are also increased in the smd1b mutant ( Fig 6D), exhibiting the same transcript accumulation as in prp8a and nsra/b mutants.…”
Section: Asco Interacts With the Spliceosome Core Components Prp8a Anmentioning
confidence: 85%